Effectiveness of Complete Systematic Land Registration Services (PTSL) at ATR/BPN Sukabumi City Land Office From 2022-2024 - Mutia Siti Damayanti; Yana Fajar FY Basori; Dian Purwanti (International Journal of Social Sciences and Humanities, 2026)
This study aims to determine the effectiveness of the Complete Systematic Land Registration Program (PTSL) services at the ATR/BPN Sukabumi City Land Office during 2022–2024. This research was motivated by the fact that there are still many community land parcels that have not been certified and the uneven achievement of the PTSL program in several areas of Sukabumi City. This study employed a qualitative method with a descriptive approach through observation, interviews, and documentation techniques. The informants consisted of the Head of the ATR/BPN Sukabumi City Land Office, PTSL implementation officers, and community members participating in the PTSL program. The study used Nugroho’s (2020) policy effectiveness theory which includes appropriate policy, appropriate implementation, appropriate target, appropriate environment, and appropriate process. The results showed that the PTSL service program at the ATR/BPN Sukabumi City Land Office has generally been quite effective, as reflected in the suitability of policies with community needs, the implementation of the program according to procedures, the increase in land certification realization in 2023 and 2024, as well as support from the government and community participation in program implementation. However, several obstacles remain, such as the lack of public understanding regarding administrative requirements, limited human resources, and uneven program achievements in several regions. Therefore, increased socialization, coordination, and equal distribution of program implementation are needed to optimize the effectiveness of PTSL services further.